Penyusunan Buku Ajar Teknik Penulisan Karya Ilmiah Bagi Mahasiswa Prodi DIII Administrasi Negara, FISH UNESA - Dian Arlupi Utami; Yuni Lestari (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2020)
Ideal learning requires the availability of maximum learning resources, one of which is the Textbook. The availability of textbooks on Scientific Writing Techniques as part of one of the teaching materials in lectures at Unesa State Administration Study Program is absolute, in order to achieve learning achievement. The purpose of this study is describing the process of compiling textbooks on the Writing Technique of Scientific Papers for D III State Administration students of FISH UNESA, as well as obstacles in the process of compiling textbooks. Data collection techniques are through interviews, observation and review by linguists and material experts. The results showed that the textbook preparation process in this study went through several stages, namely analysis, design and development, the constraints in this research process were that when this research was carried out the book was still in the form of a draft where the effectiveness of using this textbook could not be measured, several errors were found related to governance. language in the form of misspellings, typos in the arrangement.